Effects of Porosity on the Static Compression of Foam Buffer Materials of Plant Fiber and Their Numerical Model - Chongqian Huang; Xueke Zhang; Zhengqi Liu (Shock and Vibration)
In recent years, researchers have investigated plant fiber foam buffer package materials for their environmental advantages, which include their ability to completely biodegrade and their rich raw materials. The porosity of buffer materials is an important factor that affects a plant’s static compression property. In this study, foam buffer package materials of plant fiber were developed using bleached bagasse pulp as the main raw material. A digital microscope was used to observe the porosity structures of the foam buffer materials, and the porosity was calculated via binary image processing using Matlab software. The effects of porosity on the static compression properties of cushion materials were discussed, and a numerical model was established. The results indicated that the threshold value chosen affected the calculation of the porosities of buffer materials, which in turn have significant effects on their specific static compression properties. The variation trend of the stress-strain curve fits the hyperbolic tangent function, according to which a numerical model was established. The results of this experiment were in accordance with the theoretical values, which will support the theoretical design of foam buffer package materials of plant fiber.